Diagnostic Accuracy of Ultrasound to Differentiate Neoplastic and Non-Neoplastic causes of Cervical Lymphadenopathy taking Histopathology as the Gold Standard - Aqeel Shafi; Shahla Zameer; Muhammad Nauman Malik; Rabia Liaqat; Bushra Liaqat; Asiya Liaqat (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the efficacy of high-resolution ultrasound and colour Doppler in differentiating neoplastic and nonneoplastic causes of cervical lymphadenopathy compared to histopathological diagnosis.